Received Power Attenuation Analysis Based on Wavelet for Reflection-Style Optical Antenna Deformations in Free-Space Laser Communications - Wanqing Xie; Liying Tan; Jing Ma; Yang Liu (International Journal of Antennas and Propagation)
Diversified deformations on reflection-style optical antennas caused by processing technique and complex outer-space environment in free-space laser communications are modeled by wavelet analysis. Influence due to the deformations on received power is studied by distortion attenuation factor based on the model. Theoretical and numerical analysis shows that distortion attenuation factor increases with shift factor of the model, decreases with dilation factor of the model, and decreases with irregular fluctuations with wavelet coefficient of the model. To the special case that the deformation can be well approximated to a constant, distortion attenuation factor varies periodically with the linear increase of the deformation coefficient. A reference for the requirement on the precision of optical antenna is proposed, and a method to reduce the effect of deformation is recommended. It is hoped that the study can be used in the design of free space laser communication systems.